Removal of CR(VI) in wastewater by MN/AL-LDH and its modified materials - Xie, Chengrui (2020)
With the rapid development of industrialization in modern society, the excessive discharge of industrial wastewater containing chromium ions generated during industrial production has caused serious environmental pollution. In particular, Cr6+ is extremely toxic and cannot be easily removed by degradation after entering the environment. And it will accumulate and accumulate in the environment for a long time, poisoning organisms and human bodies through the food chain. At present, there are many methods for treating heavy metal-containing wastewater. The common main methods are: adsorption method, biological method, membrane separation method, chemical precipitation method and electrochemical method. Among them, the adsorption method has been widely studied and applied due to low cost and high removal rate. Common adsorbents are activated carbon, chitosan, chelate resin, and clay minerals. Clay minerals have attracted more attention and research due to its high removal rate, environmental friendliness and reusability. LDH (Layered double hydroxide) material is a typical anionic layered clay mineral. However, traditional LDH materials can only remove chromium ions through adsorption, but cannot reduce Cr6+ to less toxic Cr3+, and do not really remove the harm of Cr6+. In order to solve this problem, in this paper, a fixed ratio (Mn: Al = 2: 1) Mn/Al-LDH material was prepared by hydrothermal synthesis. At the same time, it was tried to be modified with zeolite to form a new Zeolite-Mn/Al-LDH material with higher specific surface area. At the same time, XRD, SEM, TEM and BET characterization and analysis were performed on these two materials before the adsorption reaction. The research showed that the prepared LDH had a complete crystal structure, good crystallinity, and small crystal particles. By BET characterization, it has been observed that that the BET surface area values of Zeolite-Mn-Al-LDH and Mn-Al-LDH are 47.49 ± 0.11 m2/g and 33.41 ± 0.17 m2/g. Then, the removal of Cr6+ from simulated wastewater by these two LDH materials was studied. It was observed during experiment that the modified Zeolite-Mn-Al-LDH can adsorb Cr6+ ion in solution faster than ordinary Mn-Al-LDH. When the reaction time reaches 90 min, the removal efficiencies of the two LDH are both close to 98%, respectively, which means that both two LDH can effectively remove Cr6+ in sufficient time. By comparing with past researches, it is speculated that the removal process involves the simultaneous effects of adsorption, reduction, and co-precipitation. On the one hand, hexavalent chromium is fixed to the interlayer and surface of LDH by interlayer ion exchange adsorption or surface adsorption. Subsequently, Mn2+ on the laminate will reduce Cr6+ to Cr3+. At the same time, Mn2+ will be oxidized to high-valent Mn ions, and co-precipitate with chromium in solution.